Development of replication-deficient adenovirus malaria vaccines - Michael R. Hollingdale; Martha Sedegah; Keith Limbach (Taylor & Francis Group, 2017)
Introduction: Malaria remains a major threat to endemic populations and travelers, including military personnel to these areas. A malaria vaccine is feasible, as radiation attenuated sporozoites induce nearly 100% efficacy. Areas covered: This review covers current malaria clinical trials using adenoviruses and pre-clinical research. Heterologous prime-boost regimens, including replication-deficient human adenovirus 5 (HuAd5) carrying malaria antigens, are efficacious. However, efficacy appears to be adversely affected by pre-existing anti-HuAd5 antibodies. Current strategies focus on replacing HuAd5 with rarer human adenoviruses or adenoviruses isolated from non-human primates (NHPs). The chimpanzee adenovirus ChAd63 is undergoing evaluation in clinical trials including infants in malaria-endemic areas. Key antigens have been identified and are being used alone, in combination, or with protein subunit vaccines. Gorilla adenoviruses carrying malaria antigens are also currently being evaluated in preclinical models. These replacement adenovirus vectors will be successfully used to develop vaccines against malaria, as well as other infectious diseases. Expert commentary: Simplified prime-boost single shot regimens, dry-coated live vector vaccines or silicon microneedle arrays could be developed for malaria or other vaccines. Replacement vectors with similar or superior immunogenicity have rapidly advanced, and several are now in extensive Phase 2 and beyond in malaria as well as other diseases, notably Ebola.